2022
DOI: 10.1002/uog.24827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postmortem whole‐body contrast‐enhanced microfocus computed tomography and high‐field magnetic resonance imaging of human fetuses

Abstract: What are the novel findings of this work?This is the first study to compare microfocus computed tomography (micro-CT) and high-field magnetic resonance imaging (HF-MRI) in postmortem whole-body fetal imaging. We have shown that micro-CT enables higher quality imaging, with higher resolution, image contrast and signal-to-noise ratio, compared with HF-MRI. Furthermore, the ability to recognize and assess anatomical structures is greater when using micro-CT images. What are the clinical implications of this work?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Although some institutions have used unbuffered Lugol solution for fetal staining without encountering significant tissue shrinkage [ 9 ], users should be aware that Lugol solution can cause tissue shrinkage of up to 30% [ 8 , 10 , 21 ]. This negative effect on the tissue was long thought to be the result of an osmotic imbalance between the staining solution and the fetus; however, the use of an isotonic staining solution did not prevent tissue shrinkage, thus demonstrating that osmotic imbalance is not the driving factor.…”
Section: Staining Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some institutions have used unbuffered Lugol solution for fetal staining without encountering significant tissue shrinkage [ 9 ], users should be aware that Lugol solution can cause tissue shrinkage of up to 30% [ 8 , 10 , 21 ]. This negative effect on the tissue was long thought to be the result of an osmotic imbalance between the staining solution and the fetus; however, the use of an isotonic staining solution did not prevent tissue shrinkage, thus demonstrating that osmotic imbalance is not the driving factor.…”
Section: Staining Methodsmentioning
confidence: 99%
“…This negative effect on the tissue was long thought to be the result of an osmotic imbalance between the staining solution and the fetus; however, the use of an isotonic staining solution did not prevent tissue shrinkage, thus demonstrating that osmotic imbalance is not the driving factor. Dawood et al [ 21 ] demonstrated that acidification of the solution is the key factor in soft-tissue shrinkage rather than the osmolarity of the staining solution [ 10 ]. Moreover, the authors found that staining in Lugol solution prepared with a buffer (B-Lugol) stabilizes the pH and almost completely prevents soft-tissue shrinkage, without affecting the staining time [ 10 ].…”
Section: Staining Methodsmentioning
confidence: 99%
“…HF‐MRI images are able to accurately identify anatomical structures, particularly of the heart, below 20 weeks GA 49 albeit with a lower resolution than seen with micro‐CT (137 μm in HF‐MRI vs. 22 μm in micro‐CT), 71 whilst a high concordance between HF‐MRI and CA is seen for a range of anatomical structures with sensitivity (94.6%), specificity (97.6%) and positive and negative predictive values respectively (93% and 98.2%) 112 . One study comparing CA with 9.4 and 1.5T PMMRI of the brain demonstrated that CA provided no additional information to that of HF‐MRI and where CA was non‐diagnostic, HF‐MRI could provide diagnostic information in 69% of cases 70 .…”
Section: Higher Resolution Imagingmentioning
confidence: 99%
“…More advanced post-mortem imaging techniques including High-field (HF) PMMRI and Micro-focus Computed Tomography (micro-CT) imaging 50,71,82,83 have been developed for early fetal loss, primarily to address the combined issues of poor resolution, and low signal and contrast-to-noise ratios. 41,46,49,55,57,61,71,72,82,[84][85][86][87][88]…”
Section: Higher Resolution Imagingmentioning
confidence: 99%
See 1 more Smart Citation